Proteolytic activity of human non-Hodgkin's lymphomas. - Kossakowska, A. E. (1998)
This study was conducted to assess the net proteolytic activity of human non-Hodgkin's lymphomas (NHLs). We have compared the extracellular matrix (ECM)-degradative abilities of human NHLs, reactive lymphoid hyperplasias, and established lymphoid cell lines using Matrigel invasion and elastin degradation assays. The inhibition studies allowed identification of the classes of proteinases involved in ECM degradation. Our results indicate that lymphocytes and other leukocytes derived from both human NHLs and reactive lymphoid hyperplasias are capable of Matrigel penetration, but only cells derived from the high-grade human NHLs degrade elastin in vitro. Established lymphoid cell lines (both malignant and Epstein-Barr virus immortalized) do not produce MMP-9, do not penetrate the Matrigel, and do not degrade elastin. Moreover, in human NHLs, elastolytic activity is blocked by metalloproteinase inhibitors, while inhibitors of the other classes of proteolytic enzymes have only minor effects. This study identifies metalloproteinases as the most important class of proteinases involved in ECM degradation by NHLs. The previous studies suggest that, within this class, MMP-9 represents the key enzyme that plays a role in the biological aggressiveness of human NHLs.